Development of an Evidence-Informed and Codesigned Model of Support for Children of Parents With a Mental Illness— “It Takes a Village” Approach - Goodyear, Melinda; Zechmeister-Koss, Ingrid; Bauer, Annette; Christiansen, Hanna; Glatz-Grugger, Martina; Paul, Jean Lillian (Frontiers in Psychiatry, 2022)
Providing support to parents and their children to help address the cycle of intergenerational impacts of mental illness and reduce the negative consequences for children is a key focus of selective prevention approaches in public mental health. However, a key issue for children of parents with a mental illness is the lack of access to early intervention and prevention support when needed. They are not easily identifiable (until presenting with significant mental health issues of their own) and not easily accessing the necessary support that address the complex interplay of parental mental illness within families. There are significant barriers to the early identification of these children, particularly for mental health care. Furthermore, there is a lack of collaborative care that might enhance identification as well as offer services and support for these families. The “It takes a Village” project seeks to improve mental health outcomes for children through the co-development, implementation and evaluation of an approach to collaborative practice concerned with the identification of families where a parent has a mental illness, and establishing a service model to promote child-focused support networks in Austria. Here we describe the development of service delivery approach for the “It takes a Village”, that aims to improve identification and support of these children within enhancements of the existing service systems and informal supports. The paper describes the use of codesign and other implementation strategies, applied to a research setting, with the aim of impacting the sustainability of workforce reform to achieve lasting social impact. Results highlight the steps involved in translating evidence-based components, local practice wisdom and lived experience into the practice model for Tyrol, Austria. Here we highlight how regional context-specific solutions are essential in the design of care models that meet the complex needs of these children. Service system and policy formation with local and experienced stakeholders are also vital to ensure the solutions are implementation-ready, particularly when introducing new ways of practice with vulnerable families. This also creates a solid foundation for the evaluation of the “It take a Village” approach for children of parents with a mental illness in Austria.